Seasonal distribution of species culicoides (diptera: ceratopogonidae) in konya province - Uğur Uslu; Bilal Dik (Eurasian Journal of Veterinary Sciences)
This sludy was carried out to determine seasonal distribution o I adult Culicoides species in Konya province. Samples were collected from the Culicoides breeding sites in Konya Centrum, Çumra, Kadınhanı and Saray önü from Apnl 2001 to November 2001. During the period of this investigation, 19 Culicoides species (C. drcumscriptus, C. festivipennis, C. shaklawensis, C. gejgelensis, C. puncticollis, C. nubeculosus, C. riethi, C. longipennis, C. odiatus. C. flavipulicaris. C catanen. C. submantimus. C. parroti, C. kibunensis, C. schultzei gr, C. subfasdpennıs, C. pulîcaris, C. salinariüs, C. maritimus) were identified. A total of 2798 Culicoides species (55.72 % female and 44.28 % male) were caught. The distribution ot Culicoides species by months were 0.25 % In May, 3.75 % in June, 34.13 % in July, 33.95 % in August 23.44 % in September and 4.50 % in October. No Culicoides species was captured in November.